Land use, biodiversity conservation, and rural development in the dehesas of Cuatro Lugares, Spain - Plieninger, T; Wilbrand, C (Agroforestry Systems, 2001)
Dehesas are an agrosilvopastoral system that has enhanced the maintenance of an extraordinarily high biodiversity. The traditional use is characterized by mixed livestock raising at low stocking densities, employment of hardy regional breeds and an elaborated maintenance and exploitation of holm oaks. Livestock production has traditionally been accompanied by arable systems with long rotations and closed nutrient cycles without external inputs of fodder, fertilizers and agro-chemicals. Modern trends are a specialization toward lamb and beef production and the employment of intensive techniques like freerange grazing at high stocking levels or crossbreeding with high-performance breeds. A model income statement shows that livestock create an income of 49.91 US$ per ewe per year on an average basis. The central problem for the continuity of the dehesas is the gradual decay of the tree canopy. Intensification of agricultural production and the abandonment of traditional grazing practices additionally threaten biodiversity within the dehesas. The authors suggest the foundation of a biosphere reserve in Cuatro Lugares as a framework for a sustainable development of the dehesas.
Keywords: economic output; Grazing; livestock; Mediterranean; pastoralism; Quercus ilex; rangeland

Land use, biodiversity conservation, and rural development in the dehesas of Cuatro Lugares, Spain - Plieninger, T.; Wilbrand, C. (Agroforestry Systems, 2001)
Dehesas are an agrosilvopastoral system that has enhanced the maintenance of an extraordinarily high biodiversity. The traditional use is characterized by mixed livestock raising at low stocking densities, employment of hardy regional breeds and an elaborated maintenance and exploitation of holm oaks. Livestock production has traditionally been accompanied by arable systems with long rotations and closed nutrient cycles without external inputs of fodder, fertilizers and agro-chemicals. Modern trends are a specialization toward lamb and beef production and the employment of intensive techniques like freerange grazing at high stocking levels or crossbreeding with high-performance breeds. A model income statement shows that livestock create an income of 49.91 US$ per ewe per year on an average basis. The central problem for the continuity of the dehesas is the gradual decay of the tree canopy. Intensification of agricultural production and the abandonment of traditional grazing practices additionally threaten biodiversity within the dehesas. The authors suggest the foundation of a biosphere reserve in Cuatro Lugares as a framework for a sustainable development of the dehesas.
Keywords: economic output; Grazing; livestock; Mediterranean; pastoralism; Quercus ilex; rangeland

Caractérisation de formations végétales mediterranéennes à partir de données ‘Thematic Mapper’ Une étude de cas en Andalousie (Espagne) - LACAZE, BERNARD; Joffre, Richard (International Journal of Remote Sensing, 1987)
Abstract The study is focused on the characterization of vegetation formations in a Mediterranean area (943 km2) located in southern Spain: herbaceous canopies (rangelands), shrubby vegetation (?matorral?) and complex woody/herbaceous formations (?dehesa?). Vegetation formations (physiognomical units) have been characterized by their spectral responses in the six reflective TM channels and by vegetation indices. From the ratio index TM4/TM3 there has been derived a map displaying seven classes (water, bare soil and five biomass levels reflecting the hierarchy of vegetation formations). Channels TM3, TM4 and TM5 have been considered for a supervised classification into nine land-cover categories (seven vegetation formations, bare soil and water). The proportion of correct classification of vegetation formations is about 78 per cent when considering test areas. Classification made from three principal components gives similar results.
doi: 10.1080/01431168708954777
Keywords: Automatic classification; biomass; characterization; Europe (citation); Image interpretation; land use; Mediterranean vegetation; Multispectral remote sensing; rangeland; Regional study; Satellite observation; Shrubbery; Spain; Survey; Thematic map; Vegetation type